2021
DOI: 10.3390/life11070634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Membrane Composition of Giant Unilamellar Vesicles on Their Budding Probability: A Trade-Off between Elasticity and Preferred Area Difference

Abstract: The budding and division of artificial cells engineered from vesicles and droplets have gained much attention in the past few decades due to an increased interest in designing stimuli-responsive synthetic systems. Proper control of the division process is one of the main challenges in the field of synthetic biology and, especially in the context of the origin of life studies, it would be helpful to look for the simplest chemical and physical processes likely at play in prebiotic conditions. Here we show that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…For a protocell, however, growth and division are energy-controlled processes, [212,213] where the membrane composition is also important. [214] In a thought experiment, if a spherical protocell grew by incorporation of new membrane material, its surfaceto-volume ratio would decrease. This is not possible in the physical world, since the lipid membrane has low water permeability and the volume cannot increase proportionally.…”
Section: Protocell Growth and Divisionmentioning
confidence: 99%
“…For a protocell, however, growth and division are energy-controlled processes, [212,213] where the membrane composition is also important. [214] In a thought experiment, if a spherical protocell grew by incorporation of new membrane material, its surfaceto-volume ratio would decrease. This is not possible in the physical world, since the lipid membrane has low water permeability and the volume cannot increase proportionally.…”
Section: Protocell Growth and Divisionmentioning
confidence: 99%
“…In their follow-up work they show they have control over this reaction and can reverse the initial deformation. 120 Not only enzymes can influence the membrane of liposomes, but also membranebound proteins can have an effect. Steinkühler et al showed that low densities of a membrane-bound protein can induce a curvature and this can generate strains on the membrane that lead to division (Figure 9f).…”
Section: Internally Driven Divisionmentioning
confidence: 99%
“…Interestingly, the pH increase must be accompanied by an osmotic shock (acting at the same time) to lead the vesicles to a successful budding. The higher pH inside the GUVs lumen causes oleic acid molecules to deprotonate and leave the membrane (an increase in the tension between leaflets), while the osmotic pressure deflates the vesicle (a decrease in the inner volume); the combined action of the two stimuli forces the spherical vesicles towards different equilibrium shapes until budding and/or division take place [ 104 , 105 ]. The influence of the surface-to-volume ratio on the shape of the GVs will be further detailed in the next section.…”
Section: Chemical Stimulimentioning
confidence: 99%
“…These reduced parameters can be determined in dynamic simulations as a function of time as well. For example, after a chemical stimulus, the concentration inside the vesicle can be calculated based on kinetic reaction equations, and the reduced volume and reduced area can be determined from the osmotic stress and the number of lipids in the leaflets, as, for example, was achieved for pH-induced deformations [ 99 , 102 , 104 , 105 ]. In other words, from the initial concentrations, the equilibrium shape can be determined at any time.…”
Section: Modelling and Theoretical Description Of Equilibrium Shapes ...mentioning
confidence: 99%